Brands Weigh Up Their Social Role. Issue 4 (27th October 2014) - Simpson, Anna
<x xml:space="preserve">Abstract</x> The right strategy has to span short, mid, and long‐term goals – and the overarching ambition needs to be expressed simply enough, and yet with charisma. <boxed-text content-type="graphic" id="gpol12177-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text>